Immunotherapies targeting GPRC5D in relapsed or refractory multiple myeloma: latest updates from 2022 ASH Annual Meeting - Jieyun Xia; Zhenyu Li; Kailin Xu (Journal of Hematology & Oncology, 2023)
Abstract B cell maturation antigen (BCMA)-targeted immunotherapy has shown unprecedented results in the treatment of relapsed or refractory (R/R) multiple myeloma (MM). However, disease progression remains an issue attributed to variable BCMA expression, BCMA downregulation, and heterogeneity of tumor antigens in MM. Therefore, additional treatment options with novel therapeutic targets are warranted. G protein-coupled receptor, class C group 5 member D (GPRC5D), an orphan receptor expressed on malignant plasma cells with limited expression in normal tissue, has emerged as a promising therapeutic target for R/R MM. GPRC5D-targeted chimeric antigen receptor (CAR)-T and CAR-NK cell therapy, as well as bispecific T cell engagers, offer remarkable anti-tumor activities. We summarized some latest reports on GPRC5D-targeted treatments for R/R MM from the 2022 ASH Annual Meeting (ASH 2022).